2022
DOI: 10.3390/fluids7120387
|View full text |Cite
|
Sign up to set email alerts
|

Jet Velocity and Acoustic Excitation Characteristics of a Synthetic Jet Actuator

Abstract: The effect of the excitation frequency of synthetic jet actuators on the mean jet velocity issuing from an array of circular orifices is investigated experimentally, focusing on the acoustic excitation characteristics of the actuator’s cavity. Two cavity configurations are considered. In the first configuration, synthetic jets are generated by exciting a single, large cavity having an array of sixteen orifices via sixteen piezoelectric elements. In the second configuration, the cavity volume of the first confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The noise generated by SJAs is maximized when the actuation frequency matches the Helmholtz frequency or the mechanical resonance of the diaphragm. Arafa et al [6] showed that at higher harmonics, noise generation could be lower at a minimal cost to the jet's performance. For the purposes of the current work, however, only frequencies near the Helmholtz frequency were considered.…”
Section: Acousticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The noise generated by SJAs is maximized when the actuation frequency matches the Helmholtz frequency or the mechanical resonance of the diaphragm. Arafa et al [6] showed that at higher harmonics, noise generation could be lower at a minimal cost to the jet's performance. For the purposes of the current work, however, only frequencies near the Helmholtz frequency were considered.…”
Section: Acousticsmentioning
confidence: 99%
“…Excessive noise generation can be a critical design drawback, especially in applications such as transportation, where noise reduction is a focus. Arafa et al [6] found that when designing SJA arrays, an excitation frequency away from the cavity acoustic modes should be used to ensure uniform mean jet velocity across the array. They achieved this target by dividing the SJA cavity into isolated sections.…”
Section: Introductionmentioning
confidence: 99%
“…In general, SJAs are smaller than an aircraft's wingspan, and as a result, they are used in an array form. Arafa et al [10] experimentally studied the effect of the excitation frequency of SJAs on the mean jet velocity issuing from an array of circular orifices. They focused on the acoustic excitation characteristics of the actuator's cavity.…”
mentioning
confidence: 99%